Hubungan Beban Kerja dengan Tingkat Stres Perawat di RSUD Kraton Kabupaten Pekalongan - Khusaeri Nanda Rosandi; Rahayu Winarti; Endang Supriyanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Workload refers to a series of tasks that must be completed within a specific timeframe, involving both physical and mental abilities. An imbalance between job demands and an individual’s capacity can trigger work-related stress, particularly among nurses. This study aims to analyze the relationship between workload and stress levels among nurses at Kraton Regional General Hospital in Pekalongan Regency. The study employed a quantitative correlational design with a cross-sectional approach. The sample consisted of 58 inpatient nurses selected using total sampling according to inclusion criteria. The instruments used were the Nurse Workload Questionnaire and the Extended Nursing Stress Scale (ENSS). Data analysis was conducted using univariate and bivariate methods with the Spearman Rank test. The results showed that the majority of respondents had a moderate workload (50%) and moderate stress levels (48.3%). Bivariate analysis revealed a positive and significant relationship between workload and nurses’ stress levels (r = 0.529; p < 0.05). These findings indicate that an increase in workload contributes to higher stress levels among nurses.